IMPLEMENTATION OF TRIPLE BOTTOM LINE PRINCIPLES IN INFRASTRUCTURE PROJECTS IN NORTH SULAWESI - Nicolas Willem James Mandagi; Joni Kutu’Kampilong (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
his study investigates integrating Triple Bottom Line (TBL) principles—social, economic, and environmental—into infrastructure planning and evaluation in North Sulawesi through a sequential mixed-methods design. First, a Cost–Benefit Analysis (CBA) estimated Net Present Value (IDR 45.2–85.4 billion), Benefit–Cost Ratio (1.1–1.8), and Internal Rate of Return (9.5 % over 30 years), confirming economic viability. Simultaneously, a Life Cycle Assessment (LCA) quantified material-related energy use and CO₂e emissions, while structured surveys and focus-group discussions captured community perceptions of benefit distribution and participation. These quantitative and qualitative insights were synthesized in a Multi-Criteria Decision Analysis (MCDA) employing the Analytic Hierarchy Process (AHP), where twelve experts assigned weights of 0.441 (social), 0.301 (environmental), and 0.258 (economic). Among three strategic alternatives, a low-emission public-private partnership scored highest (0.83) by combining robust stakeholder engagement, recycled-steel use with offset mechanisms, and strong long-term returns; sensitivity analysis (±10 % environmental weight) confirmed its ranking stability. By mapping outcomes to SDG 9 (Industry, Innovation and Infrastructure), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action), the study demonstrates that a TBL-based framework can simultaneously secure financial performance, advance social equity, and reduce environmental impact. Recommendations include formalizing hybrid financing, enhancing participatory platforms, and incentivizing low-carbon materials.